Association between body mass index and mortality for colorectal cancer survivors: overall and by tumor molecular phenotype - Campbell, Peter T. (Cancer Epidemiol Biomarkers Prev, 2015)
BACKGROUND: Microsatellite instability (MSI) and BRAF-mutation status are associated with colorectal cancer survival whereas the role of body mass index (BMI) is less clear. We evaluated the association between BMI and colorectal cancer survival, overall and by strata of MSI, BRAF-mutation, sex, and other factors. METHODS: This study included 5,615 men and women diagnosed with invasive colorectal cancer who were followed for mortality (maximum: 14.7 years; mean: 5.9 years). Pre-diagnosis BMI was derived from self-reported weight approximately 1-year before diagnosis and height. Tumor MSI and BRAF-mutation status were available for 4,131 and 4,414 persons, respectively. Multivariable hazard ratios (HR) and 95% confidence intervals (CIs) were estimated from delayed-entry Cox proportional hazards models. RESULTS: In multivariable models, high pre-diagnosis BMI was associated with higher risk of all-cause mortality in both sexes (per 5-kg/m(2), HR = 1.10; 95% CI = 1.06 to 1.15), with similar associations stratified by sex (p-interaction: 0.41), colon vs rectum (p-interaction: 0.86), MSI status (p-interaction: 0.84), and BRAF-mutation status (p-interaction: 0.28). In joint models, with MS-stable/MSI-low and normal BMI as the reference group, risk of death was higher for MS-stable/MSI-low and obese BMI (HR: 1.32; p-value: 0.0002), not statistically significantly lower for MSI-high and normal BMI (HR: 0.86; p-value: 0.29), and approximately the same for MSI-high and obese BMI (HR: 1.00; p-value: 0.98). CONCLUSIONS: High pre-diagnosis BMI was associated with increased mortality; this association was consistent across participant subgroups, including strata of tumor molecular phenotype. IMPACT: High BMI may attenuate the survival benefit otherwise observed with MSI-high tumors.